Comparison of Oxford Knee Score in Knee Osteoarthritis Patients Before and After Total Knee Replacement at Dr. Mohamad Soewandhie Hospital - Santosa, Sharlene Joy; Sasono, Bimo; Sekarputri, Cempaka Harsa; Rambung , Etha ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: One of the most common degenerative joint diseases is knee osteoarthritis. This condition leads to pain and reduces functionality of the knee joints, which can negatively impact a patient’s quality of life. Total knee replacement (TKR) has become the standard procedure to treat end-stage osteoarthritis. Evaluating the success of TKR procedures is very important. One instrument that can be used for this purpose is the Oxford Knee Score (OKS). Methods: This observational analytic comparative study involved 40 patients. The data were collected by interviewing patients who had undergone TKR at Dr. Mohamad Soewandhie General Hospital between 2019 and 2024. The data were analyzed using Wilcoxon signed-ranks test, independent samples t-test, and Kruskal-Wallis test.  Results: The majority of the sample in this study was aged over 60 years (62.5%), female (87.5%), and had an overweight BMI (47.5%). The analysis showed a significant increase in the OKS after surgery, with a p-value of <0.05. The independent samples t-test showed a significant difference in the improvement of the OKS between males and females. Meanwhile, the Kruskal-Wallis test showed no significant difference in OKS improvement across BMI categories. Conclusions: There is a significant difference in the OKS before and after TKR surgery, which indicates an improvement in knee functionality and quality of life after surgery. Differences in patient gender may affect the outcome of the surgery, including post-surgery recovery rate and knee functionality. Meanwhile, BMI showed no significant difference in the outcome of TKR surgery.